Sexual morality defaced and defied: socio-legal and religious perspectives - Ansari, Abdul Haseeb; Ahmad, Muhamad Hassan; Sinha, Manoj Kumar; Jamal, Parveen (Serials Publications (P) Ltd., 2019)
It is not correct to say that traditionalists, who are spiritual and love to practice social traditions based on their religions, are opposing homosexuality (gay-sex) and wish to retain it as an offence. They simply want to uphold religious norms vis-à-vis social norms. On the other hand, people with progressivism as well as modernism are pleading for demolishing the parting wall between heterosexuality and homosexuality by declaring gay-sex as morally as well as legally acceptable in the name of sexual equality and protection of rights of LGBT communities; and stressing for decriminalising homosexuality. In between the two, there exists a modest class, which wants to retain the criminal character of homosexuality but wish to enforce the law only in extreme cases, where there is a danger that social morality will erode because of homosexual behavior in particular cases. The Indian Supreme Court in its recent judgment declared section 377 of the Indian Penal Code to be violative to the equality clause and the clause guaranteeing dignity to citizens, thus, ultra vires to the Constitution. Some say it is a purely technical decision merely enforcing ‘constitutional morality’ without taking into consideration the ‘social morality’, which considers it as a despicable and socially deviant human behavior. It has actually defied and defaced the sexual morality of the Indian society. On the contrary, the Apex Court of Singapore enforced ‘social morality’ and ruled to retain section 377A of the Penal Code of Singapore. And the Policymakers of the country took mild stand on the enforcement of this criminal provision. The paper discusses the social and religious aspects, and the judicial solicitude on the matter of sexual morality and concludes that courts acting as the ‘guardian of morality’, should give due consideration to the religious, social and moral aspects of homosexuality in the society.